BAHASA INDONESIA âDISTURBSâ IN ACQUISITION OF BALINESE AS A SECOND LANGUAGE - Yeni Andriyani, Ni Putu (Lingual: Journal of Language and Culture, 2015)
This article aims at finding how Bahasa Indonesia interferes Balinese as a second language to the kid who speak Bahasa Indonesia as her mother tongue. The result shows that the interference of Bahasa Indonesia occurred in the use of vocabulary, including the class of verbs, noun, adjective, possessive pronoun, and adverb. The child mostly used the lexicons from Bahasa Indonesia in referring to the Balinese lexicons. The interference may happen because Bahasa Indonesia is spoken more occasionally than Balinese in daily conversation, including at home, school, as well as communicating with friends.